Aviation Archaeology Offshore: The Recovery of a Rare Ju88 Aircraft Wreck during Work for the New London Gateway Port. Issue 2 (May 2015) - Scott, Graham; Gane, Toby
<x content-type="archive" xml:space="preserve">Abstract</x> During dredging works for the new London Gateway Port in 2011, fragments of a German Ju 88 bomber were recovered from the Thames Estuary. Subsequent archaeological investigation by Wessex Archaeology, using geophysical survey and divers, resulted in the location of the wreck site and its subsequent recovery under licence in 2012. Post-recovery analysis has enabled it to be identified as a very rare prototype Ju 88T. The aircraft, flown by men of the secretive Luftwaffe special operations unit VOdL, was lost during a reconnaissance mission to record bomb damage at Chelmsford in 1943. The Norwegian fighter ace who shot it down, Marius Eriksen, subsequently achieved fame as a Norwegian skiing champion and actor. The recovery was unusual in that it was carried out as a staged archaeological investigation and in the context of offshore development, where 'avoidance' is the usual strategy.